Fezolinetant- A novel NK3R antagonist for treating postmenopausal vasomotor symptoms - Saqib Ali; Muhammad Affan Ilyas (Journal of the Pakistan Medical Association, 2024)
Madam, It has been estimated that up to 80% of postmenopausal women experience vasomotor symptoms (VMS) such as hot flushes, night sweats, mood swings and difficulty in concentrating1. These symptoms markedly affect different aspects of daily life for women, including, sleep, mental well-being, sex, interpersonal communication and overall quality of life (QOL). Furthermore, they cause a significant burden on healthcare and workplace productivity. Hormone therapy (HT), involving combined estrogen and progesterone or estrogen alone, is the standard management for VMS associated with menopause. However, safety and tolerability issues have discouraged the use of HT, due to the associated risk of breast cancer, stroke and venous thromboembolism2. Alternative treatments, including selective serotonin reuptake inhibitors (SSRIs), clonidine, gabapentin, and herbal remedies, have demonstrated limited effectiveness with undesirable side effects like sedation and nausea3. This situation warrants a safe and effective non-hormonal therapy for managing menopause-associated VMS. Neurokinin-3 receptor (NK3R) antagonists offer a unique therapeutic approach with minimal adverse effects (AEs). This class of drugs functions by inhibiting the stimulation of KNDy neurons, thereby restoring the normal function of the thermoregulatory centre, which is altered by reduced estrogen levels and subsequent unopposed action of the neuropeptide neurokinin B on NK3 receptors located on KNDy neurons in the hypothalamus4, 5. In 2023 the United States Food and Drug Administration, has,approved the first ever NK3R antagonist, Fezolinetant, (Veozah) for VMS in postmenopausal women. The approval was granted following two phase 3, double-blind placebo controlled trials: SKYLIGHT 1 and 2. The efficacy of the drug was tested for 12 weeks including women aged between 40 and 65 with confirmed menopause and at least 7 episodes of hot flushes a day. Vasomotor symptoms , like hot flushes and night sweats, were effectively improved in the control group with beneficial effects on sleep. The most common AE was a headache. Other infrequent and non-serious AEs included abdominal pain, nausea, fatigue and oropharyngeal pain4, 5 NK3R antagonists are an innovative class of drugs that are an effective therapeutic option for postmenopausal symptoms with better efficacy and safety. Availability of the oral form of these drugs makes it an easier option for postmenopausal women, improving overall QOL. —Continue